FAKTOR PERADABAN ISLAM ERA SAHABAT NABI HINGGA ZAMAN KONTEMPORER - Sabarudin, Mohammad; Al Ayyubi, Ibnu Imam; rohmatulloh, Rifqi; Nasrulloh, Inas (Sekolah Tinggi Ilmu Adab dan Budaya Islam Riyadul 'Ulum, 2022)
The dynamics of Islamic civilization is a concept that refers to the development of civilization or culture based on Islamic principles. This concept involves renewal, adaptation, and transformation in various aspects of life, which usually include social, economic, political, and cultural aspects, taking into account the values ​​of life, ethics, and Islamic principles. The method used in this research is a descriptive research method with a literature study approach that refers to several research data sources and data collection techniques in the form of studies of Islamic cultural civilization. The focus of the research will be raised is the dynamics of Islamic civilization in the era of the companions of the Prophet. The data collection technique used in this study was the library research method, namely the study of literature originating from books and articles in journals, the data analysis technique used in this study was a descriptive method. Islam is a religion that has concrete concepts and rules prohibiting how to form a civilization and the process of forming a civilization in the development of human life, there are at least three primary factors derived from the development and decline of a civilization. This can provide imagination in carrying out effective and efficient disruption to various fields of economic, educational, political, and cultural aspects